Pemanfaatan Augmented Reality (AR) untuk Pembelajaran Bahasa Inggris bagi Siswa SMA IT Imam Syafi’i Cendikia Pekanbaru - Ilyas, Muhammad; Putri, Miranti Eka; Effendi, Leo Adhar; Fahlevi, Reza; Fatricia, Niken (Pakis Journal Institute, 2026)
This community service program aimed to improve English learning autonomy and digital literacy skills of 11th-grade students of SMA IT Imam Syafi’i Cendikia Pekanbaru through the use of Augmented Reality (AR)-based learning applications. This issue was raised due to the low level of independence in learning English and digital literacy among Year 11 students at Imam Syafi'i Cendikia Islamic High School in Pekanbaru. The English learning process still tends to rely on teacher explanations and textbooks, so students are not accustomed to learning independently and utilising digital technology optimally.The activity was conducted through three stages: preparation, implementation, and continuous mentoring. The preparation stage involved needs analysis, interviews with English teachers, and material development based on the school curriculum. The implementation phase was carried out through digital media socialization, demonstration, and direct practice using AR applications to support vocabulary mastery, pronunciation, and daily communication. A total of 30 students participated actively in the training and were guided to operate the digital learning applications independently. The final stage involved online mentoring through WhatsApp, email, and phone communication to ensure learning sustainability. This implementation proves that reality ‘enhanced’ through AR is not merely a tool, but a new ecosystem that improves the quality of language education. This technology is considered highly feasible, with a feasibility rating of 93.13% from media experts. Although this simulation is hyperrealistic, its educational impact on students' motivation, confidence, and linguistic mastery is very real.